Life : selected quotations - Coelho, Paulo frey50; Hagesther, Anne Kristin (New York HarperCollins Publishers, 2007)
A volume of selected quotes, culled from the author's extensive body of work, offers insight into his spiritual perspectives on the nature of existence.
The dream -- The path -- Love -- Chance -- The journey -- Destiny -- The good fight -- The mystery.
Keywords: Coelho, Paulo -- Quotations